Psychological and Physiological Stress in Hens With Bone Damage - Rokavec, Neža; Zupan Šemrov, Manja (Frontiers in Veterinary Science, 2020)
Abnormalities in bone development in humans and nonhumans can lead to impaired physical and psychological health, however, evidence is lacking regarding the role of individual psychosocial factors in the development of poor bone conditions. Addressing this lack of knowledge, we used low-productive laying hens (n = 93) and assessed behavioral responses to an open-field test (at 17, 18, 29, 33 weeks of age; wa), an aerial predator test (at 39 wa), and a social reinstatement test (at 42 wa). Bone condition was assessed using a palpation technique on five occasions (at 16, 29, 33, 45, 58 wa), with the half of the hens experiencing damage (deviations, fractures or both) at 29 wa and all hens by 58 wa. Stress-induced corticosterone concentration in feathers (at 16, 33, 58 wa) and body weight (at 23, 47, 58 wa) were also investigated. We hypothesized that lighter birds (at 23 wa) with the higher corticosterone (at 16 wa) and open-field-induced fear collected before the onset of lay (at 17 and 18 wa) are associated with a worse bone condition when in lay. We also hypothesized that those birds with more damage at the peak of laying (at 29 wa) would be lighter at 47 and 58 wa and more fearful by showing higher open-field (at 29 and 33 wa) and predator-induced fear responses, however, acting less socially towards conspecifics. These hens were also expected to have the higher corticosterone (at 33 and 58 wa). Our results show no association between fear level and open-field fear behavior, corticosterone concentration or body weight on the one hand (all measured before starting to lay) and bone damage at 29 wa on the other. When in lay, bone damage was associated with more pecking and less crossing zones when faced with an open field situation at 29 wa and improved sociality at 42 wa. This study provides the first evidence of a relationship of bone health with fear, sociality, and stress response. When in poor bone condition, our hens had enhanced psychological stress measured by fear behavior reactivity but not physiological stress measured as feather corticosterone concentration.